2015
DOI: 10.1186/s12970-014-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a pre-loaded multi-ingredient performance supplement on muscle soreness and performance following downhill running

Abstract: The effects of multi-ingredient performance supplements (MIPS) on perceived soreness, strength, flexibility and vertical jump performance following eccentric exercise are unknown. The purpose of this study was to determine the impact of MIPS (NO-Shotgun®) pre-loaded 4 weeks prior to a single bout of downhill running (DHR) on muscle soreness and performance. Trained male runners (n = 20) were stratified by VO2max, strength, and lean mass into two groups; MIPS (n = 10) ingested one serving daily of NO-Shotgun® f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(95 reference statements)
1
10
0
Order By: Relevance
“…Köhne and colleagues [ 64 ] explored the effects of a MIPS on flexibility, muscle damage, and power in female runners who performed a single bout of downhill running during the mid-follicular phase following 28 days of supplementation. Though Köhne and colleagues did not find any differences between MIPS and placebo with regard to any outcome measure, these results are very similar to a study performed in men using a nearly identical study design and the same supplement [ 56 ]. Another study using only female participants found that MIPS did not influence RMR or body composition when compared to placebo [ 66 ], though menstrual control was not mentioned in the manuscript.…”
Section: Chronic Effects Of Mips On Performancesupporting
confidence: 78%
See 3 more Smart Citations
“…Köhne and colleagues [ 64 ] explored the effects of a MIPS on flexibility, muscle damage, and power in female runners who performed a single bout of downhill running during the mid-follicular phase following 28 days of supplementation. Though Köhne and colleagues did not find any differences between MIPS and placebo with regard to any outcome measure, these results are very similar to a study performed in men using a nearly identical study design and the same supplement [ 56 ]. Another study using only female participants found that MIPS did not influence RMR or body composition when compared to placebo [ 66 ], though menstrual control was not mentioned in the manuscript.…”
Section: Chronic Effects Of Mips On Performancesupporting
confidence: 78%
“…Blend 4: (376 mg) Caffeine 30 min prior to exercise or immediately upon waking on off days. NA Skinfolds, perceived soreness VAS, ROM, vertical jump, isokinetic and isometric strength using isokinetic dynamometer, VO 2max , before and after a single bout of downhill running 1 ↔ Isometric and isokinetic strength ↔ Flexibility ↔ Power ↔ Perceived soreness [ 56 ] Köhne et al 2016 8 trained female runners Double-blind, placebo controlled, 28-day supplementation study b Prop. Blend 1: (9660 mg) Casein Protein Whey Protein BCAAs L-arginine Prop.…”
Section: Chronic Effects Of Mips On Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Due to the varied ingredient profile of these supplements and prevalence of proprietary blends, the efficacy and mechanism of action can vary substantially between individual supplement formulations [151]. Ormsbee et al [152] found no effect of 31 days of MIPS consumption (21 g/day) on functional and biochemical measures of EIMD after downhill running in trained male runners. A later study by the same group [17] using a cohort of trained female runners found that prophylactic consumption of the same MIPS (21 g/day for 28 days) likewise had no effect on markers of damage after a similar exercise stimulus.…”
Section: Main Textmentioning
confidence: 99%